2018
DOI: 10.1186/s12884-017-1649-1
|View full text |Cite
|
Sign up to set email alerts
|

Experiences with and expectations of maternity waiting homes in Luapula Province, Zambia: a mixed–methods, cross-sectional study with women, community groups and stakeholders

Abstract: BackgroundLuapula Province has the highest maternal mortality and one of the lowest facility-based births in Zambia. The distance to facilities limits facility-based births for women in rural areas. In 2013, the government incorporated maternity homes into the health system at the community level to increase facility-based births and reduce maternal mortality. To examine the experiences with maternity homes, formative research was undertaken in four districts of Luapula Province to assess women’s and community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
87
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(91 citation statements)
references
References 13 publications
4
87
0
Order By: Relevance
“…The findings of our study on health care expenditures for delivery care among MWH users than nonusers and associated factors could not directly be compared with other previous studies on MWH in Ethiopia or other countries because those studies had no comparisons of health care expenditures for delivery care among MWH users and nonusers . Studies on the costs of using MWHs are limited, and further studies are needed to understand the approximate amount of fees and their effect on the use of these facilities . We found that mode of delivery, the distance from home to facility, and type of transportation were independent factors for higher OOP payments.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The findings of our study on health care expenditures for delivery care among MWH users than nonusers and associated factors could not directly be compared with other previous studies on MWH in Ethiopia or other countries because those studies had no comparisons of health care expenditures for delivery care among MWH users and nonusers . Studies on the costs of using MWHs are limited, and further studies are needed to understand the approximate amount of fees and their effect on the use of these facilities . We found that mode of delivery, the distance from home to facility, and type of transportation were independent factors for higher OOP payments.…”
Section: Discussionmentioning
confidence: 63%
“…6,10,14,15 Studies on the costs of using MWHs are limited, and further studies are needed to understand the approximate amount of fees and their effect on the use of these facilities. 28 We found that mode of delivery, the distance from home to facility, and type of transportation were independent factors for higher OOP payments. A study from Ethiopia reported that the higher rates of CS among MWH users could potentially increase OOP expenses.…”
Section: Discussionmentioning
confidence: 71%
“…Several studies have prioritised the need to improve facilities and quality of care at the MWH and lower barriers to increase MWH utilisation . This study, however, found that the quality of care at the health facility is more important.…”
Section: Discussionmentioning
confidence: 81%
“…These were useful for analysis of providers' and users' perspectives, but less appropriate for describing the interrelatedness of these perspectives and the complex interplay of factors impacting on access to MWHs. Several studies have prioritised the need to improve facilities and quality of care at the MWH and lower barriers to increase MWH utilisation [21,[25][26][27][28]. This study, however, found that the quality of care at the health facility is more important.…”
Section: Discussionmentioning
confidence: 92%
“…This study utilized a cross-sectional, concurrent triangulation mixed-methods design to cross-validate findings. 16 , 17 Data for this analysis were collected for the baseline observation of an impact evaluation (NCT 02620436) 40 of a maternity waiting home (MWH) intervention designed from formative research 18 21 being implemented in 40 primary health facility catchment areas (HFCAs) within seven districts across Zambia. A quantitative HHS was administered and qualitative IDIs were conducted concurrently to triangulate and corroborate findings ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%